Bridging Tradition and Modernity: Al-Syāṭibī’s Maqāṣid al-Sharī‘ah as a Framework for Contemporary Islamic Jurisprudence - Zainuddin Sunarto (Al-Qalam Institute, 2025)
This study examines the concept of Maqāṣid al-Sharī‘ah as understood by al-Syāṭibī and its relevance to the development of contemporary Islamic law. Al-Syāṭibī, a key figure in the development of maqāṣid theory, introduced a systematic approach through his seminal work al-Muwāfaqāt. Using a qualitative method with a library research approach, this study analyses both primary and secondary sources, including the works of al-Syāṭibī and reviews from contemporary Islamic legal scholars. The findings reveal that al-Syāṭibī categorises maqāṣid into three levels: ḍarūriyyāt (essential), ḥājiyyāt (complementary), and taḥsīniyyāt (enhancing), focusing on the protection of five fundamental values: religion, life, intellect, lineage, and property. Al-Syāṭibī’s maqāṣid approach not only provides normative guidance but is also responsive to social dynamics. The implications of this study suggest that a deep understanding of maqāṣid can serve as a methodological foundation for formulating Islamic laws that are both contextual and solution-oriented, addressing the issues of modern society.